(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article examines the prospects for implementing innovative technologies in teaching, the modern understanding of innovative technologies, and their role and significance. It considers the challenges of using various teaching methods in problem-based learning, problem-solving, finding solutions to situations, and the prospects of innovative technologies. The effectiveness of informatization and digitalization of the educational process is discussed, which should create a firm conviction that these qualities of organizing the educational process are characteristic of modern society. The article also explores designing learning by the requirements of the time, as well as using and developing logical thinking skills.